Pengaruh Model Pembelajaran Search, Solve, Create, and Share dan Predict Observe Explain terhadap Hasil Belajar Biologi Siswa Kelas VIII SMPN 1 Gondangrejo Karanganyar Tahun Ajaran 2013/2014 - Djumadi Djumadi; Erfan Budi Santoso (Jurnal VARIDIKA, 2014)
This study has objectives (1) to know the effect of SSCS learning model and POE toward the achievement of students learning biology, (2) the difference between the achievement of students learning biology using SSCS learning model and POE. This is quasi experimental research with randomized subjects posttest only control group design. The population are three classes randomly selected from SMP Negeri 1 Gondangrejo Karanganyar 2013/2014. The first class, VIIID, is thaught by POE learning model. The second class is SSCS learning model, and the third, as control class, is thaught by variative lecturing. Data are collected by test, quessionaire, observation, and documentation.Then data are analysed by validity, reliability, difficulty test index. The results are (1) there is an effect of SSCS learning model and POE toward the achievement of students learning biology at three aspects: cognitive, affective and psychomotoric. It can be seen on the average of students learning achievement at experiment class and control class with the significance value 0,05. The proceed result of anova Post Hoc test Scheffe indicates that there is a difference the achievement of students learning biology using SSCS learning model and POE at affective and psichomototic domain, but it does not happen in cognitive domain. The conclusion is (1) there is an effect of the achievement of students learning biology using SSCS learning model and POE, (2) SSCS learning model is more effective than POE.